INSURANCE LAWS & PRACTICES IN THE UNITED STATES OF AMERICA AND SOUTH AFRICA: INSIGHTS FOR NIGERIA - Toby, Boma Geoffrey; Akani, Nnamdi Kingsley; Onuoha, Anugbum (PEOPLE: International Journal of Social Sciences, 2020)
The United States of America (US) is one of the largest financial markets, and houses the most mature and viable insurance sector in the world, with a huge population and well developed technologically advanced insurance sector. Insurance as part of the finance sector added 21% to the GDP of the financial institutions in the US. Similarly, in the Republic of South Africa (SA), though smaller in population to the US and Nigeria, SA enjoys a robust insurance sector with the latest Insurance Act 2018 to help the sector and the economy. Nigeria, on the other hand is much larger in terms of size and population to SA, being over 200million in population, but with a weak insurance sector and the Insurance Act 2004 is the primary legislation sustaining insurance practice in the 36 states of Nigeria. This paper examines the prospects, challenges and pitfalls of these experienced sectors, with a view to gaining useful insights into their insurance laws and practices for useful guide that can benefit the Nigerian insurance industry and made recommendations that attention must be given to Nigerian Insurance law, by way of a review and an amendment for growth of the industry. Digital and technological infrastructure, though presently at its nascent stages in Nigeria, must be fully explored if the sector is to realize its full potential, while attention must be given to the cost and over-dependence on digital and tech innovations to avoid their pitfalls.